Relationship between body mass index and cardiovascular metabolic multimorbidity: a systematic review and meta-analysis - Wu, Min; Huang, Yanyan; Liu, Qinyu (Frontiers in Cardiovascular Medicine, 2025)
This study aimed to systematically evaluate the association between body mass index (BMI) and cardiovascular metabolic multimorbidity (CMM). Cochrane Library, CINAHL, EMBASE, Web of Science, and PubMed were searched for observational studies examining the relationship between BMI and CMM, with a search timeframe from database inception to May 16, 2024. The Newcastle-Ottawa Scale (NOS) and the Agency for Healthcare Research and Quality (AHRQ) criteria were used to evaluate the quality of included studies. The meta package in R was used to perform a meta-analysis. Subsequently, pooled odds ratios (OR) and their 95% confidence intervals (CIs) were computed. Eleven (11) studies involving 1,771,748 patients were included in this review, and the meta-analysis was conducted based on 10 studies. The meta-analysis revealed that when BMI was analyzed as a categorical variable, both overweight (pooled OR = 3.52, 95% CI: 1.23–10.05) and obesity (pooled OR = 3.68, 95% CI: 2.60–5.20) were significantly associated with CMM. When BMI was treated as a continuous variable, it was also significantly related to CMM (pooled OR = 2.90, 95% CI: 1.99–3.81). Furthermore, obesity was associated with an increased risk of CMM [hazard ratio (HR) = 3.27, 95% CI: 2.44–3.39]. This study highlighted a positive correlation between overweight/obesity and CMM. Consequently, it is essential to enhance health awareness among high-risk populations, such as older adults and those with obesity. Proactive screening for high-risk individuals and increased public education on CMM are recommended. Weight management strategies should be integrated into CMM management plans for obese patients to reduce the incidence of these conditions.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, PROSPERO CRD42024602835.